The integration of geospatial analyses based on AI in GIS in the context of the “15-minute city” concept - Grădinaru Anca Patricia; Badea Ana-Cornelia; Ene Anca; Badea Gheorghe (E3S Web of Conferences)
The “15-minute city” concept is an urban planning model that aims to ensure all essential services are accessible within a 15-minute walk or bike ride in order to reduce the reliance on cars and to offer a sustainable approach to urban living, contributing to the achievement of green and inclusive smart cities. AI (Artificial Intelligence) tools can provide the means to obtain a quick and efficient response in analysing urban geospatial data and can make data analysis a process available even for non-specialist users. Integrating AI-driven geospatial analysis in GIS can significantly enhance the planning and implementation of this concept, by providing precise, real-time data and predictive insights. The aim of this article is to analyse the possibilities of geospatial data management and analysis using AI tools, within the context of the “15-minute city”, to contribute to the process of obtaining green and inclusive smart cities.